Pendekatan Kuantitatif dan Kualitatif Filsafat Ilmu Untuk Penelitian Psikologi - MM. Nimas Eki Suprawati (Jurnal Orientasi Baru, 2009)
Psychology has been gaining a good reputation in science and society. Ithas contributed positively to the human life and progress. But as a growingscience, psychology has both external and internal problems. One of them isreflected in the dispute on the quantitative and qualitative paradigm used byits scientists. What psychology should do and which attitudes its scientistsshould have? It is important that its scientist starts by acknowledging his orher identity. Then, the next important thing is to rethink about the natureof psychology itself. How does psychology come into existence? How hasit been growing? What is its uniqueness? Psychologists themselves have toconsider seriously the scientific nature of their knowledge as well as theirscientific attitudes. Philosophy of science will help to clarify and explain thedisputed problem.